The Effects of Mergers and Acquisitions on Banks’ Performance in Tanzania: Case of NCBA, NIC, CBA: Mergers and acquisition on Banks' Performance - Msalilwa, Gloria; Mwenda, Beny (Cita Konsultindo Research Center, 2024)
This study investigated the effects of mergers and acquisitions (M&A) on the performance of banks in Tanzania, specifically focusing on NCBA Bank, formed from the merger of NIC Bank and CBA Bank. The study aimed to assess the impact of M&A on key performance variables, including the Capital Adequacy Ratio (CAR), Asset Quality Ratio, and Current Ratio, with financial performance measured through Return on Assets (ROA). Adopting a time series research design within a quantitative approach, the study utilized a census sampling technique on all M&A banks in Tanzania, focusing on NCBA Bank due to its significant assets. Data were collected from financial statements spanning ten years (2014-2023) and analyzed using SPSS software, applying regression analysis to test hypotheses. The findings revealed that while liquidity positively influenced financial performance, asset quality showed a negative effect, and the capital base did not significantly impact performance. The study concluded that M&A could enhance bank performance if effectively managed. Recommendations included improving asset quality and liquidity management strategies to optimize financial outcomes in the Tanzanian banking sector.